Austerity and the path of least resistance: how fiscal consolidations crowd out long-term investments. Issue 4 (3rd April 2021) - Jacques, Olivier
ABSTRACT: What policies do government prioritize when they implement austerity? I argue that governments choose the path of least resistance when they engage in fiscal consolidations. Positive policy feedback protects programmes from retrenchment when they cover large segments of the population. In contrast, policies involving discounting short-term benefits for long-term gains are more exposed to austerity as they are subject to an intertemporal trade-off. Using a compositional dependent variable analysis in 17 OECD countries from 1980 to 2014, I show that austerity, measured with the narrative approach to fiscal consolidations, is associated with a decrease in the proportion of public investment in research and development and gross fixed capital formation and an increase in health care and pensions' proportion of budgets. The budget shares of human capital investments in education, childcare and active labour market policies and of compensatory transfer-based labour market insurance are resilient to austerity.